2018
DOI: 10.1016/j.geomphys.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Einstein’s field equations as a fold bifurcation

Abstract: It is shown that Einstein's field equations for all perfect-fluid k = 0 FLRW cosmologies have the same form as the topological normal form of a fold bifurcation. In particular, we assume that the cosmological constant is a bifurcation parameter, and as such, fold bifurcation behaviour is shown to occur in a neighbourhood of Minkowski spacetime in the phase space. We show that as this cosmological constant parameter is varied, an expanding and contracting de Sitter universe emerge via this bifurcation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The dynamical analysis can be enriched further with using the biffurcation theory methods. Recently, the problem of bifurcations in the FRW cosmology with perfect fluid and the cosmological constant was investigated in the work of Kohli and Haslam [14]. They demonstrated that as the cosmological constant parameter is varied, expanding de Sitter and contracting de Sitter universes emerge via fold bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical analysis can be enriched further with using the biffurcation theory methods. Recently, the problem of bifurcations in the FRW cosmology with perfect fluid and the cosmological constant was investigated in the work of Kohli and Haslam [14]. They demonstrated that as the cosmological constant parameter is varied, expanding de Sitter and contracting de Sitter universes emerge via fold bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Bogdanov-Takens bifurcations have been shown to occur in Bianchi IX cosmological models in the frame work of Gauss-Bonnet gravity [11]. A more recent study [12] has also demonstrated the occurrence of such a bifurcation in Friedmann-Roberston-Walker (FRW) cosmology in the presence of cosmological constant without considering viscosity. The latter study is of limited scope due to neglecting viscosity which is a real physical dissipative effect which is essential for getting certain desirable properties of Bogdanov-Takens system such as the finiteness of the number of fixed points.…”
Section: Introductionmentioning
confidence: 96%
“…The latter study is of limited scope due to neglecting viscosity which is a real physical dissipative effect which is essential for getting certain desirable properties of Bogdanov-Takens system such as the finiteness of the number of fixed points. Up to the best of our knowledge, the works in [11,12] are the only two instances in cosmological studies where the Bogdanov-Takens bifurcations occurred. In fact, investigating and classifying all possible solutions and their stability properties in cosmological models enhances our understanding of the models.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ref. [32] shows that in FRW-models with perfect fluids and the cosmological constant, the expanding and contracting deSitter Universe arise as bifurcation. It is worth mentioning that interesting bifurcation scenarios were reported in the Randall-Sundrum braneworld model [33], interacting Veneziano ghost DE [34], Brans-Dicke model [35], nonminimal coupled scalar field model [31,36] etc.…”
Section: Introductionmentioning
confidence: 99%